Anti-CTLA-4 based therapy elicits humoral immunity to galectin-3 in patients with metastatic melanoma. (3rd July 2018) - Wu, Xinqi; Giobbie-Hurder, Anita; Connolly, Erin M.; Li, Jingjing; Liao, Xiaoyun; Severgnini, Mariano; Zhou, Jun; Rodig, Scott; Hodi, F. Stephen
ABSTRACT: The combination of CTLA-4 blockade ipilimumab (Ipi) with VEGF-A blocking antibody bevacizumab (Bev) has demonstrated favorable clinical outcomes in patients with advanced melanoma. Galectin-3 (Gal-3) plays a prominent role in tumor growth, metastasis, angiogenesis, and immune evasion. Here we report that Ipi plus Bev (Ipi-Bev) therapy increased Gal-3 antibody titers by 50% or more in approximately one third of treated patients. Antibody responses to Gal-3 were associated with higher complete and partial responses and better overall survival. Ipi alone also elicited antibody responses to Gal-3 at a frequency comparable to the Ipi-Bev combination. However, an association of elicited antibody responses to Gal-3 with clinical outcomes was not observed in Ipi alone treated patients. In contrast to being neutralized in Ipi-Bev treated patients, circulating VEGF-A increased by 100% or more in a subset of patients after Ipi treatment, with most having progressive disease. Among the Ipi treated patients with therapy-induced Gal-3 antibody increases, circulating VEGF-A was increased in 3 of 6 nonresponders but in none of 4 responders as a result of treatment. Gal-3 antibody responses occurred significantly less frequently (3.2%) in a cohort of patients receiving PD-1 blockade where high pre-treatment serum Gal-3 was associated with reduced OS and response rates. Our findings suggest that anti-CTLA-4 elicited humoral immune responses to Gal-3 in melanoma patients which may contribute to the antitumor effect in the presence of an anti-VEGF-A combination. Furthermore, pre-treatment circulating Gal-3 may potentially have prognostic and predictive value for immune checkpoint therapy.